CONTEMPORARY INTERPRETATION OF CHRONIC DISEASES OF THE TRANSIENT NOSE AND NOSE SIDE SPACES WITH CHRONIC DACRYOTYSISTITIS - Burkhanov Ulugbek.; Rakhmonkulov Umedjon.; Norpulotov Kurbonali. (Western European Studies, 2024)
Tear separation is a fairly significant group among all eye diseases and is distinguished by the fact that it occupies a high place in the structure of diseases. According to a number of authors, 8-25.6% of outpatients suffer from lacrimation.Among patients treated in an inpatient setting for diseases of the organs of vision, this indicator is from 7.45% to 10%. As a rule, the pathology of the horizontal part of the tear ducts is observed more than the vertical part. Therefore, the percentage of pathologies of the horizontal part (tear points, tear ducts) is 75 to 85%. Pathology of the vertical part, in particular, the lacrimal sac itself and the nasolacrimal duct, is relatively rare and occurs in 5-13% of cases
Keywords: the lacrimal sac; lacrimal ducts; inflammation